Analysis of Students' Parents Consent on Face-to-Face Learning Activities During the Covid-19 Pandemic - Mirza Ghulamudin (JELLE : Journal Of English Literature, Linguistics, and Education, 2021)
Covid-19 still overshadows all activities of Indonesian society so that all activities carried out outside the home are limited through Government policy. Likewise, the activities of students at school were replaced by distance learning. All students learn from their homes via their smartphones, whether it's their own, or their parents or siblings. Distance Learning Activities have been carried out from March 2020 to February 2021, although face-to-face learning has been carried out several times. However, due to the situation and conditions that were still dangerous from the Covid-19 attack, Distance Learning was carried out again. This makes students less optimal in obtaining subject matter from the teacher, because they often get assignments rather than material. When the teacher gave the material, the students were only given the subject matter title, then asked the students to learn on their own. So that the attitude of boredom of students in Distance Learning activities was formed during the Covid-19 Pandemic. They spend more time playing online games and social media applications than on studying. Then a survey of students 'parents' consent was conducted so that Face-to-Face Learning was carried out so that learning activities could take place immediately, and students could get the maximum learning material. Keywords: Student Parent Consent, Face-to-Face Learning, Covid-19 Pandemic.